Targeting the CXCL12/CXCR4 pathway and myeloid cells to improve radiation treatment of locally advanced cervical cancer. Issue 5 (5th March 2018) - Lecavalier‐Barsoum, Magali; Chaudary, Naz; Han, Kathy; Koritzinsky, Marianne; Hill, Richard; Milosevic, Michael
Abstract : Cervical cancer is the fourth most commonly diagnosed cancer and the fourth leading cause of cancer death in women worldwide. Approximately half of cervical cancer patients present with locally advanced disease, for which surgery is not an option. These cases are nonetheless potentially curable with radiotherapy and cisplatin chemotherapy. Unfortunately, some tumours are resistant to treatment, and lymph node and distant recurrences are major problems in patients with advanced disease at diagnosis. New targeted treatments that can overcome treatment resistance and reduce metastases are urgently needed. The CXCL12/CXCR4 chemokine pathway is ubiquitously expressed in many normal tissues and cancers, including cervical cancer. Emerging evidence indicates that it plays a central role in cervical cancer pathogenesis, malignant progression, the development of metastases and radiation treatment response. Pre‐clinical studies of standard‐of‐care fractionated radiotherapy and concurrent weekly cisplatin plus the CXCR4 inhibitor Plerixafor (AMD3100) in patient‐derived orthotopic cervical cancer xenografts have shown improved primary tumour response and reduced lymph node metastases with no increase in early or late side effects. These studies have pointed the way forward to future clinical trials of radiotherapy/cisplatin plus Plerixafor or other newly emerging CXCL12 or CXCR4 inhibitors in women with cervical cancer.